Effects of Tillage on Soil Nutrients and Yield of Winter Wheat in Dry Loess Tableland (Bangladesh Journal of Botany, 2023)
An experiment was carried out to find out whether long-term no-tillage poses a threat to soil fertility and crop yield at the Changwu Loess Plateau Agricultural Ecological Experiment Station of Northwest A&F University in Changwu County, Shaanxi Province. Before seeding winter wheat in September 2020, the three tillage methods, namely no-tillage, conventional and rotational tillage were conducted on the experimental field that had undergone three consecutive years of no-tillage. After the winter wheat harvest in 2021, total soil nutrients, available soil nutrients, and wheat yield in the soil layer of 0-30 cm were analyzed under various tillage methods. Results showed a decreasing trend in the contents of total nitrogen and soil organic carbon (SOC) in the soil layer of 0-30 cm under three tillage methods. The SOC content and total nitrogen in the 0-10 cm layer were no tillage > rotation tillage > conventional tillage. The contents of P and K decreased with an increase in the layer of 0-30 cm soil depth under the three tillage methods. The available P and K contents were decreased by 16.07, 32.74, 15.54 and 27.08%, respectively in the soil layer of 10-20, 20-30 cm, compared to those in the layer of 0-10 cm (P < 0.05). Using various tillage methods, the content of available P under conventional tillage was significantly reduced by 11.31% in the 0-10 cm layer compared to that under no-tillage. Soil available k content under conventional tillage and rotation tillage decreased significantly by 6.16 and 4.97% compared to no tillage (P < 0.05), respectively. In the layer of 20-30 cm soil, available P content was significantly increased under conventional tillage by 18.12% compared to that under no-tillage, and available K contents were significantly increased under conventional tillage by 17.17 and 9.22% compared to that under no-tillage and rotation tillage, respectively (P < 0.05). The winter wheat yield was in the order of conventional tillage > rotational tillage > no-tillage, with a significant difference between conventional and no-tillage (P < 0.05). Therefore, it is necessary to carry out proper conventional tillage or rotary tillage on the dry loess tableland where no-tillage has been carried out for a longer time.Bangladesh J. Bot. 51(4): 931-936, 2022 (December) Special